Epidemiology of bacterial meningitis among children in Brazil, 1997-1998 - Débora PL Weiss; Paul Coplan; Harry Guess
OBJECTIVE: To document the incidence and the descriptive epidemiology of bacterial meningitis among individuals under age 20 in a geographically defined region in Brazil during the two-year period immediately preceding the introduction of Haemophilus influenzae type b (Hib) vaccines into the national immunization program of Brazil. METHODS: Population-based epidemiological study of all cases of bacterial meningitis reported among residents of Campinas, Brazil, under age 20 (n=316,570) during the period of 1997-98, using comprehensive surveillance records compiled by the Campinas Health Department from cases reported among hospital inpatients, outpatients, emergency room visits, death certificates, and autopsy reports. RESULTS: The incidence of bacterial meningitis (n=274) was 334.9, 115 and 43.5 cases/10(5) person-years (pys) for residents of Campinas under age 1, 5 and 20, respectively. All cases were hospitalized, with an average length of stay of 12 days. Documented prior antibiotic use was 4.0%. The case-fatality rate of bacterial meningitis in individuals under age 20 was 9% (24/274) with 75% of deaths occurring in children under the age of five. The incidence of Hib meningitis (n=26) was 62.8 and 17 cases/10(5) pys in children age <1 and <5, respectively. CONCLUSIONS: The incidence of Hib meningitis in children under the age of 5 in Campinas during 1997-98 was similar to that reported in the US, Western Europe, and Israel prior to widespread Hib vaccine use in those regions. This study provides a baseline for later studies to evaluate changes in the etiology and incidence of bacterial meningitis in children after introduction of routine Hib vaccination in Brazil.